The Inuit Qaujimajatuqangit Health System: A Holistic, Strength-based, and Health-promoting Model from and for Inuit Communities - Healey Akearok, Gwen; Mearns, Ceporah; Mike, Nancy (Études Inuit Studies, 2023)
Public health models are important frameworks for guiding public health action. Although numerous public health models are found in the literature, a dearth of models focus on the health paradigms of Indigenous communities, globally, yet no models are derived from Inuit health perspectives and knowledge. Inuit Qaujimajatuqangit is an all-encompassing term that refers to Inuit knowledge and practices across time. Using a mixed-method, narrative analysis approach, the Inuit Qaujimajatuqangit Health System Model has emerged as a holistic, trauma- and resilience-informed, strength-based, and community-grounded public health model. This model can serve as a guide for systems change as well as public health interventions, health programs, clinical services, patient-oriented research, health human-resource modeling, and health policy for Inuit communities.